2007
DOI: 10.1152/japplphysiol.01167.2006
|View full text |Cite
|
Sign up to set email alerts
|

Limiting sarcolemmal Na+entry during resuscitation from ventricular fibrillation prevents excess mitochondrial Ca2+accumulation and attenuates myocardial injury

Abstract: overload yielding levels that corresponded to 77% and 71% of control hearts at VF/CC and PR, without differences among specific Na ϩ -limiting interventions. Limiting sarcolemmal Na ϩ entry attenuated reductions in left ventricular compliance during VF and prompted higher mean aortic pressure (110 Ϯ 7 vs. 95 Ϯ 11 mmHg, P Ͻ 0.001) and higher cardiac work index (159 Ϯ 34 vs. 126 Ϯ 29 g ⅐ m ⅐ min Ϫ1 ⅐ kg Ϫ1 , P Ͻ 0.05) with lesser increases in circulating cardiac troponin I at 60 min PR. Conclusions: Na ϩ -limiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 62 publications
1
53
0
1
Order By: Relevance
“…Its effect on myocardial carbon dioxide concentration is not clear. Be that as it may, elegant studies of cardiac arrest induced by ventricular fibrillation revealed improvement in cardiac function during fibrillation [25] and significant attenuation of postresuscitation ventricular arrhythmias including prevention of recurrent episodes of ventricular fibrillation with cariporide and other NHE1 inhibitors in both pig and rat models (table 1) [26,27,28,29,30,31,32]. …”
Section: Cardiac Arrestmentioning
confidence: 99%
“…Its effect on myocardial carbon dioxide concentration is not clear. Be that as it may, elegant studies of cardiac arrest induced by ventricular fibrillation revealed improvement in cardiac function during fibrillation [25] and significant attenuation of postresuscitation ventricular arrhythmias including prevention of recurrent episodes of ventricular fibrillation with cariporide and other NHE1 inhibitors in both pig and rat models (table 1) [26,27,28,29,30,31,32]. …”
Section: Cardiac Arrestmentioning
confidence: 99%
“…It was previously reported that NHE-1 inhibitors attenuate myocardial reperfusion injury by limiting sodium-induced cytosolic and mitochondrial calcium overload, and thereby help preserve left ventricular distensibility during chest compression and attenuate post-resuscitation myocardial dysfunction 12 . In this study, the NHE-1 inhibitor cariporide (1 mg/kg), which had been extensively investigated in the past, was compared with the newer compound AVE4454B (1 mg/kg) and vehicle control in three groups of 10 rats each, all subjected to 10 min of untreated VF followed by 8 min of chest compression before delivering electrical shocks.…”
Section: Representative Resultsmentioning
confidence: 99%
“…29 Sodium-hydrogen exchanger inhibitors Animals/rat-heart model Decrease in peri-arrest arrhythmias, amelioration of ischaemic contracture, improvement of myocardial performance post-ROSC. 37,38 Humans, RCT Cariporide decreased MI rates but increased cerebrovascular events and short term mortality after CABG 39,40 Erythropoietin Animals Increase in coronary and mean aortic perfusion pressure and reduction of adrenaline dose during CPR. Improvement of cardiac performance and short-term survival after CA.…”
Section: ␤-Blockersmentioning
confidence: 99%